Imaging Findings of Primary Non-functioning Hepatic Paraganglioma: A Case Report - Feng, Yuan Wei; Xiang, Zhao Xin (Current Medical Imaging, 2018)
Most paragangliomas are located in adrenal glands but 22% arise from extra-adrenal position. Primary hepatic paragangliomas are rare tumors and their imaging features have not been documented in detail in radiology literatures. We describe a case of pathologically proven primary non-functioning hepatic paraganglioma, which revealed a heterogeneously enhancing mass with internal cystic degeneration misdiagnosed as HCC or FLHCC on contrast-enhanced CT and MRI, restricted diffusion on DWI and ADC mapping and abundant vascularity on 3D-CTA.
Keywords: Hepatic paraganglioma